Biochar addition to organo-mineral fertilisers delays nutrient leaching and enhances barley nutrient content. Issue 13 (10th November 2023) - Llovet, Alba; Vidal-Durà, Andrea; Alcañiz, Josep Maria; Ribas, Angela; Domene, Xavier
ABSTRACT: Biochar, a carbon-rich solid produced from biomass pyrolysis, has attracted growing interest as a fertiliser ingredient due to its ability to non-permanently retain nutrients. A greenhouse pot experiment was set up to compare three commercial organo-mineral fertiliser formulations (NPK, NP and K) with the corresponding formulations containing a slow-pyrolysis wood biochar (NPK+B, NP+B and K+B) (6 replications each). Nutrient leaching as well as crop growth and nutrient uptake was monitored using barley as model species. Nutrient leaching was slowed down in the NPK+B compared to the NPK fertiliser. The most responsive ions were nitrate and potassium, whose leaching during the two first weeks was reduced by 28% and 22%, respectively, while this trend reversed from the third week on. One plausible explanation would be a microbial nutrient immobilisation mediated by the concurrent NPK and biochar habitat provision. NPK+B significantly enhanced barley straw biomass (23.43% increase respect to NPK), whereas all the biochar-based fertilisers showed increases in nutrient content and export (involving potassium, sulphur, calcium and manganese), possibly indicating that biochar acted as a nutrient source. These results provide some evidence of the potential use of the studied biochar in biochar-based fertilisers to meet nutrient availability with plant demands.